Potential Roles of Cyber-ethical Awareness in Mitigating Plagiarism in the Usage of Chatbot Technologies among Students: A Review - Aderinola Ololade Dunmade; Timilehin Olasoji Olubiyi; Olorundamisi Daniel Dunmade (International Journal of Small and Medium Enterprises and Business Sustainability, 2023)
In recent decades, academic dishonesty (plagiarism) has been a prevalent issue and of grave concern to the academic community, prompting numerous researchers to conduct studies aimed at identifying the myriad of factors that contribute to the malady. The study explores the influence of cyber-ethical awareness on mitigating plagiarism in the use of chatbot technologies among Nigerian undergraduate students. It begins by introducing the concepts of cyberethics, plagiarism, and chatbot technologies. The review then examines the relationship between chatbot technologies and academic integrity, highlighting the factors that contribute to plagiarism in this context. Additionally, it investigates the prevalence of plagiarism among Nigerian undergraduate students. The review also explores the connection between cyber-ethical awareness and plagiarism, emphasizing the importance of fostering cyber-ethical awareness to reduce instances of plagiarism. It examines the existing level of cyber-ethical awareness among Nigerian undergraduate students and discusses the role of such awareness in preventing plagiarism. Furthermore, the review presents various strategies to promote cyber-ethical awareness. These include educational initiatives aimed at educating students about the responsible use of technology, the establishment of institutional policies and guidelines to discourage plagiarism, and the use of technology-based solutions to detect and prevent plagiarism. In conclusion, the review emphasizes the significance of promoting cyber-ethical awareness among Nigerian undergraduate students to address the issue of plagiarism in the use of chatbot technologies. By fostering an understanding of ethical practices in technology use, universities can enhance academic integrity and ensure a culture of responsible scholarship.